Types and Functions of Hedges and Boosters in Graduate Students’ Research Articles - Vebriyanto, Danu Angga; Mujiyanto, Januarius (Universitas Negeri Semarang, 2019)
Hedges and Boosters are important rhetorical devices for increasing or reducing the force of claims in academic writing. Compared to other aspects rhetorical patterns or devices in research articles, quite surprisingly the use of hedges and boosters in research articles has attracted little attention from researchers. This study aimed to investigate the use of hedges and boosters employed by graduate students in research articles. This study was a descriptive qualitative study of twenty research articles written by graduate students aiming at revealing the realization of types and functions of hedges and boosters as well as their relations based on the taxonomy of Hyland (1998) and Salager-Meyer (1997). The strategies were elaborated into five sub-research questions to seek for types, functions, and relation of hedges and boosters. The objects of the study were the research articles written by graduate students. The data were gathered through documentation. The findings revealed that there were seven types of hedges and eight types of boosters employed by students. Dealing with the functions of hedges and boosters, it was discovered that the graduate students employed four functions of hedges and three functions of hedges. Moreover, it was discovered that hedges and boosters tend to be clustered together to create harmonic combination. the present study suggests the EFL lecturers to pay attention to the significance of hedges and boosters to enrich the students’ knowledge on the parts of discourse. It might become references for advisors to have many attentions on the students under their guidance.